Research on the Public Opinion Guidance Mechanism of Major Public Health Incidents - Wang, Yuqi; Wu, Rui; Zeng, Jun; Xue, Peiyi (Frontiers in Psychology, 2022)
Public opinion guidance is a crucial part in the management of major public health incidents, and exploration of its mechanism is conducive to the comprehensive governance of social security. The current study conducts a case study on the anti-pandemic public opinion guidance and analyzes the public opinion representation and the internal mechanism of public opinion guidance in the context of the COVID-19 in China to objectively analyze the general rules of public opinion guidance. The research findings suggest that the public opinion on the COVID-19 in China manifested a three-stage progressive and stable tendency and witnessed the strength of China, benefiting from the systematic and complete integration and release mechanism for anti-pandemic information, the three-dimensional mechanism for the dissemination of knowledge related to pandemic prevention and health, the innovative disclosure mechanism for precise information, as well as diversified channels for international public opinion guidance. The guidance mechanism proposed in this study is of great significance to the public opinion guidance of global major public health incidents in the future.